Lung function in primary Sjögren's syndrome: a cross sectional and longitudinal study. Issue 3 (March 1991) - Kelly, C; Gardiner, P; Pal, B; Griffiths, I
Abstract : Clinical and radiological assessment of 100 patients (97 female) with primary Sjögren's syndrome was performed within six months of diagnosis in conjunction with spirometry and measurement of transfer factor for carbon monoxide (TLCO). This was repeated in an unselected subgroup of 30 patients after a mean interval of four years. On initial assessment, 43 patients had symptoms of lung disease and 10 had related physical signs; the chest radiograph was abnormal in five. There was a significant reduction (more than 2 standardised residuals) in forced expiratory volume in one second (FEV1), vital capacity (VC), and TLCO in 14, 12, and 10 patients, 24 patients overall having a significant reduction in one or more of these measures. There was a strong relation between reduction in lung function and both pulmonary symptoms and a lip biopsy specimen positive for Sjögren's syndrome. Lung function at the initial assessment in the 30 patients who were restudied was almost identical to that of the group as a whole. Seventeen now had symptoms and nine had related physical signs. The chest radiograph was abnormal in four patients. More patients had a significant reduction in FEV1, VC, and TLCO. Lung disease is sometimes an early feature of primary Sjögren's syndrome and may progress over a relatively short period.